2008
DOI: 10.1007/s10456-008-9101-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin in angiogenesis and vascular diseases

Abstract: Endoglin is a transmembrane auxillary receptor for transforming growth factor-beta (TGF-beta) that is predominantly expressed on proliferating endothelial cells. Endoglin deficient mice die during midgestation due to cardiovascular defects. Mutations in endoglin and activin receptor-like kinase 1 (ALK1), an endothelial specific TGF-beta type I receptor, have been linked to hereditary hemorrhagic telangiectasia (HHT), an autosomal dominant vascular dysplasia characterized by telangiectases and arteriovenous mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
208
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(218 citation statements)
references
References 122 publications
(170 reference statements)
4
208
1
5
Order By: Relevance
“…Also, in clinical development as an antitumor agent is a chimeric antibody (TRACON) capable of neutralizing endoglin (CD105; ref. 31), a proangiogenic protein in the TGFb superfamily that binds BMP9/BMP10 (22,45,46), with loss-of-function mutations resulting in another type of vascular dysplasia, HHT-1 (15,47). In patients with advanced, refractory tumors (31), anti-endoglin antibody was associated with infusion reactions and immunogenicity distinct from effects described for dalantercept in the present study, whereas other adverse effects such as anemia and telangiectasias were observed in both studies.…”
Section: Discussionmentioning
confidence: 37%
“…Also, in clinical development as an antitumor agent is a chimeric antibody (TRACON) capable of neutralizing endoglin (CD105; ref. 31), a proangiogenic protein in the TGFb superfamily that binds BMP9/BMP10 (22,45,46), with loss-of-function mutations resulting in another type of vascular dysplasia, HHT-1 (15,47). In patients with advanced, refractory tumors (31), anti-endoglin antibody was associated with infusion reactions and immunogenicity distinct from effects described for dalantercept in the present study, whereas other adverse effects such as anemia and telangiectasias were observed in both studies.…”
Section: Discussionmentioning
confidence: 37%
“…Endoglin is highly expressed on the cell membranes of syncytiotrophoblasts, vascular endothelial cells, and it is also expressed on other cells such as monocytes and hematopoietic stem cells [49][50][51][52]. Given that, Endoglin is suggested to involve in angiogenesis and hematopoiesis and play a role in cancer and cardiovascular development [53,54]. In human, mutations in the Endoglin gene cause hereditary hemorrhagic telangiectasia or Osler Rendu Weber Syndrome type 1 (HHT1), an autosomal-dominant disorder characterized by arteriovenous malformations in multiple organ systems and bleeding telangiectases of mucous membranes [54].…”
Section: Soluble Endoglinmentioning
confidence: 99%
“…Given that, Endoglin is suggested to involve in angiogenesis and hematopoiesis and play a role in cancer and cardiovascular development [53,54]. In human, mutations in the Endoglin gene cause hereditary hemorrhagic telangiectasia or Osler Rendu Weber Syndrome type 1 (HHT1), an autosomal-dominant disorder characterized by arteriovenous malformations in multiple organ systems and bleeding telangiectases of mucous membranes [54].…”
Section: Soluble Endoglinmentioning
confidence: 99%
“…33,34 Interestingly, endoglin modulates endothelial NO synthase (eNOS) expression and activity, thus affecting vascular tone. [35][36][37] In the present study, we hypothesized that lower concentrations of relevant markers of NO formation (plasma and whole blood nitrite) would be found in hypertensive disorders of pregnancy compared with those found in healthy pregnancies. In addition, given the fact that sFLT-1 and sEng interfere with eNOS activity, we hypothesized that inverse relationships exist between the circulating concentrations of markers of NO formation and sFLT-1 or sEng during pregnancy.…”
mentioning
confidence: 92%